Modeling the Effect of Moss Cover on Soil Temperature and Carbon Fluxes at a Tundra Site in Northeastern Siberia. Issue 9 (22nd September 2018) - Park, Hotaek; Launiainen, Samuli; Konstantinov, Pavel Y.; Iijima, Yoshihiro; Fedorov, Alexander N.
Abstract: Mosses strongly affect water and heat fluxes due their high water holding capacity and the provision of insulation. A land surface model (the coupled hydrological and biogeochemical process model, CHANGE) was used to quantitatively assess the influence of moss cover on soil temperature ( T SOIL ), active layer thickness (ALT), and ecosystem carbon balance. The CHANGE model was coupled with a moss process module, enabling the explicit representation of heat, water, and carbon exchange in the atmosphere‐vegetation‐moss‐soil system. The model was applied to a tundra site in northeastern Siberia over the period of 1980–2013. The results were validated with in situ observations and indicated a high level of insulation by the moss, resulting in warmer winter and cooler summer T SOIL and smaller ALT. The sensitivities of T SOIL and ALT to moss coverage and thickness were examined using model experiments. An increase in moss thickness lowered the summer T SOIL by 0.9–2.1 °C and reduced ALT by 9–20 cm compared with a moss‐free experiment. The moss‐induced cooler T SOIL in the root zone could limit the productivity of vegetation by reducing water availability to plant roots due to the presence of ice. This limitation increased with increasing moss layer thickness and coverage. The productivity of the moss itself increased with thickness, partially offsetting the reduction in vegetation productivity. Our modeling study suggests that the moss layer has a significant impact on T SOIL, ALT, and carbon balance in the Arctic tundra and may play an important role in future Arctic warming. Key Points: Assessing the influences of moss cover on soil temperature, active layer thickness, and carbon flux feedback at a tundra site Moss‐induced lower soil temperature limits carbon flux trough lower soil water availability due to the presence of ice